Multisite biologic tissue SARS-CoV-2 PCR testing in kidney transplantation from a COVID-positive donor. Issue 7 (5th July 2022) - Zhang, Jared R; Kueht, Michael; Lea, A Scott; Stevenson, Heather L; Gosnell, Joseph; Ren, Ping; Nielsen, Marisa C; Miller, Aaron; Mujtaba, Muhammad; Fair, Jeffrey
Abstract: With a high community transmission rate, SARS-CoV-2 has profoundly exacerbated the shortage of organs. Although the risk of donor-recipient transmission of SARS-CoV-2 is anecdotally low, an organ-specific infection analysis of procured organs from SARS-CoV-2 positive donors has yet to be established. Using a combination of clinically available and research-only polymerase chain reaction methods, organ preservation fluid and renal parenchymal tissues were tested for SARS-CoV-2 from the kidney of a SARS-CoV-2-positive donor prior to transplantation. The recipient has remained SARS-CoV-2 negative and clinically well, with excellent graft function 120 days post-transplantation.